Lithium nickelate positive electrode material and preparation method and application thereof

CN119547223APending Publication Date: 2025-02-28ZHONGKE ZHILIANG NEW ENERGY MATERIALS (ZHEJIANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050770.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-09-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing lithium nickelate cathode materials are difficult to balance cycle stability and thermal stability while increasing energy density. Traditional lithium-rich cathode materials have poor material interface stability due to high voltage charging, which affects cycle life.

Method used

The chemical formula of lithium nickelate cathode material is Li1+xNi1-xO2, 0.02≤x≤0.08. It has an α-NaFeO2 type hexagonal layered structure and an R-3m type crystal structure. The molar ratio of Li to Ni is slightly greater than 1:1. The octahedral voids occupied by Li in the Ni layer are randomly distributed and prepared through molten salt chemistry, which avoids the existence of c/2m units and ensures the slightly lithium-rich state of the material.

Benefits of technology

It achieves high energy density, excellent cycle stability and high thermal stability among lithium-ion batteries. It can reach an energy density of >900Wh/kg when charged to 4.3V, and maintains a discharge specific capacity of 92.3% under 100 cycles and high rates. , the thermal runaway temperature reaches 253.2°C, significantly improving the performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547223A_ABST
    Figure CN119547223A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium nickelate positive electrode material and a preparation method and application thereof, the chemical formula of the positive electrode material is Li < 1 + x > Ni < 1-x > O2, and x is greater than or equal to 0.02 and less than or equal to 0.08; the crystal structure is an alpha-NaFeO2 type hexagonal layered structure, and the space group is R-3m type. Redundant Li relative to the stoichiometric ratio of Ni occupies octahedral voids in the Ni layer and is randomly distributed in the octahedral voids. The preparation method comprises the following steps: (1) reacting a nickel source and a lithium source with oxygen in the presence of a fused salt additive to obtain a product containing lithium nickelate; and (2) purifying the product containing the lithium nickelate to obtain powder containing the lithium nickelate, and placing the powder in an oxygen environment to obtain the lithium nickelate positive electrode material. When the positive electrode material is used for the lithium ion battery, high energy density, excellent cycling stability and excellent thermal stability can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

A lithium nickelate positive electrode material and its preparation method and application Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a lithium nickelate positive electrode material and a preparation method and application thereof. Background Art

[0002] Ternary materials represented by lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide can provide good energy density and power density, and have been widely used in the manufacture of power batteries. Increasing the nickel content can increase the energy density of the ternary positive electrode material, but it will reduce the cycle stability and thermal stability of the material. Lithium nickel oxide (LiNiO2) has a high energy density (>900Wh / kg material layer), but it is not easy to obtain a phase that conforms to the theoretical stoichiometric ratio during the synthesis of this type of material, and it is usually lithium-deficient (the ratio of the amount of Li and Ni is less than 1). During the electrochemical cycle, the material is prone to structural transformation from a layered phase to a rock salt phase, and is also prone to losing lattice oxygen, so the cycle stability is poor, and the structural transformation also leads to poor rate performance. In order to improve the energy density, the existing technology has proposed a variety of lithium-rich cathode materials (usually the ratio of the amount of Li and transition metal substances is greater than 1.1:0.9). However, the traditional lithium-rich cathode materials are composed of two structural units, namely R-3m (layered structure LiMO2, M=Ni, Co, Mn and other transition metals) and c / 2m (monoclinic structure Li2MO3, M=Mn, Co, or Ni) structural units. However, materials containing c / 2m units (Li2MO3 units, M=Mn, Co or Ni) need to be charged to a high voltage (>4.5V vs Li due to their thermodynamic properties). + / Li) in order to intercalate and deintercalate a large number of lithium ions and achieve high energy density. Such high voltage exceeds the stability window of the electrolyte, resulting in poor material interface stability and shortening its cycle life. In other words, existing cathode materials have difficulty achieving high energy density, excellent cycle stability, and excellent thermal stability.

[0003] Summary of the Invention

[0004] In view of the shortcomings and deficiencies of the prior art, the present invention provides a lithium nickelate positive electrode material, which, when used in lithium-ion batteries, can simultaneously have high energy density, excellent cycle stability and thermal stability.

[0005] In order to solve the above technical problems, a technical solution adopted by the present invention is as follows:

[0006] A lithium nickelate positive electrode material, the chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-xO2, wherein 0.02≤x≤0.08; the crystal structure of the lithium nickelate positive electrode material is an α-NaFeO2 type hexagonal layered structure, and the space group of the crystal structure of the lithium nickelate positive electrode material is R-3m type; in the crystal structure of the lithium nickelate positive electrode material, Li that is in excess relative to the stoichiometric ratio of Ni occupies the octahedral voids in the Ni layer in the layered structure and is randomly distributed in the octahedral voids.

[0007] The molar ratio of Li to Ni in the lithium nickelate positive electrode material is slightly greater than 1:1, and the positive electrode material is in a slightly lithium-rich state.

[0008] In some embodiments, 0.03≤x≤0.06.

[0009] In some embodiments, 0.04≤x≤0.05.

[0010] In some embodiments, no Li2NiO3 units with a space group of c / 2m are detected in the crystal structure using neutron diffraction.

[0011] The present invention also provides a lithium nickelate positive electrode material, the chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-x O2, wherein 0.02≤x≤0.08; the crystal structure of the lithium nickelate positive electrode material is an α-NaFeO2 type hexagonal layered structure, and the space group of the crystal structure is R-3m type.

[0012] In some embodiments, 0.03≤x≤0.06.

[0013] In some embodiments, 0.04≤x≤0.05.

[0014] In some embodiments, in the crystal structure of the lithium nickelate positive electrode material, Li that is stoichiometrically surplus relative to Ni occupies the octahedral voids in the Ni layer in the layered structure and is randomly distributed in the octahedral voids.

[0015] In some embodiments, no Li2NiO3 units with a space group of c / 2m are detected in the crystal structure using neutron diffraction.

[0016] In the present invention, no superstructure peak is observed during the neutron diffraction test, that is, no Li2NiO3 unit with a space group of c / 2m is detected. Therefore, it can be determined that the crystal structure of the lithium nickelate positive electrode material does not contain a Li2NiO3 unit with a space group of c / 2m.

[0017] The present invention also provides a lithium nickelate positive electrode material, the chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-xO2, wherein 0.02≤x≤0.08, the lithium nickelate positive electrode material is prepared by a preparation method comprising the following steps: (1) reacting a nickel source and a lithium source with oxygen in the presence of a molten salt additive to obtain a product containing lithium nickelate; (2) purifying the product containing lithium nickelate to obtain a powder containing lithium nickelate, and placing the powder in an oxygen environment to obtain the lithium nickelate positive electrode material.

[0018] In the present invention, the molten salt additive refers to an additive that can form a eutectic mixture with a lower eutectic point with the lithium source in the reaction raw materials. The molten salt additive can be a lithium-containing molten salt or a lithium-free molten salt.

[0019] The present invention also provides a method for preparing the aforementioned lithium nickelate positive electrode material, which can stably prepare a slightly lithium-rich lithium nickelate positive electrode material. The preparation method comprises the following steps:

[0020] (1) reacting a nickel source and a lithium source with oxygen in the presence of a molten salt additive to obtain a product containing lithium nickelate;

[0021] (2) Purifying the product containing lithium nickelate to obtain a powder containing lithium nickelate, and placing the powder in an oxygen environment to obtain the lithium nickelate positive electrode material.

[0022] The product containing lithium nickelate obtained in the aforementioned step (1) generally contains, in addition to lithium nickelate, an excess of lithium source and molten salt additives.

[0023] The purification step in the aforementioned step (2) can remove excess lithium source and molten salt additives, but this process may cause damage to the surface structure of lithium nickelate. Placing the powder in an oxygen environment in step (2) can repair the surface structure of lithium nickelate, so that the crystal structure of the final lithium nickelate positive electrode material has a perfect layered structure with a space group of only R-3m.

[0024] In some embodiments, the nickel source is selected from one or more of NiO, Ni(OH)2 or NiCO3.

[0025] In some embodiments, the lithium source is selected from LiOH or LiOH·H2O.

[0026] The molten salt additive is selected from one or more of Li2SO4, Na2SO4 and K2SO4.

[0027] In some embodiments, the molten salt additive is Li2SO4.

[0028] In some embodiments, the molar ratio of the lithium source to the nickel source is 1.1-1.7:1.

[0029] In some embodiments, the molar ratio of the lithium source to the nickel source is 1.3-1.5:1.

[0030] In some embodiments, the molar ratio of the molten salt additive to the nickel source is 0.1-0.5:1.

[0031] In some embodiments, the molar ratio of the molten salt additive to the nickel source is 0.27-0.5:1.

[0032] In some embodiments, in step (1), the reaction temperature is 550-650°C.

[0033] In some embodiments, in step (1), the reaction time is 10-20 hours.

[0034] In some embodiments, in step (2), the temperature of the oxygen environment is 450-550°C.

[0035] In some embodiments, in step (2), the time of placing in the oxygen environment is 2-5 hours.

[0036] In some embodiments, in step (2), the purification includes washing with water and filtering.

[0037] In some embodiments, the method further comprises a step of pulverizing the product containing lithium nickelate before the purification.

[0038] In some embodiments, the method comprises the following steps:

[0039] (1) uniformly mixing a nickel source, a lithium source, and a molten salt additive to obtain a mixture, placing the mixture in a reactor, introducing oxygen into the reactor, and heating the reactor to react to obtain a product containing lithium nickelate;

[0040] (2) The product containing lithium nickelate is crushed, washed with water, and filtered to obtain a powder containing lithium nickelate. The powder is placed in a reactor, oxygen is introduced into the reactor, and the temperature is increased to obtain the lithium nickelate positive electrode material. The aforementioned water washing can remove excess lithium source and molten salt additive.

[0041] In some embodiments, in step (1), the flow rate of the oxygen is 0.1-0.5 L / min.

[0042] In some embodiments, in step (1), the heating rate is 2-10°C / min.

[0043] In some embodiments, in step (1), the reaction is followed by cooling, and preferably, the cooling rate is 2-10°C / min.

[0044] In some embodiments, in step (2), the flow rate of the oxygen is 0.1-0.5 L / min.

[0045] In some embodiments, in step (2), the heating rate is 2-10°C / min.

[0046] In some embodiments, in step (2), the temperature is further cooled after the temperature is increased. Preferably, the cooling rate is 2-10°C / min.

[0047] In some embodiments, the reactor is a tube furnace.

[0048] The present invention also provides the use of the aforementioned lithium nickelate positive electrode material in a lithium ion battery.

[0049] The present invention also provides a lithium-ion battery comprising a positive electrode comprising the aforementioned lithium nickelate positive electrode material. In some embodiments, the lithium-ion battery has a first discharge energy density of greater than or equal to 904 Wh / kg at a 0.1C rate.

[0050] In some embodiments, after 100 charge and discharge cycles of the lithium-ion battery at a rate of 1C in a voltage range of 4.3-2.8V, the discharge specific capacity retention rate is greater than or equal to 92.3%.

[0051] In some embodiments, the thermal runaway temperature T2 of the lithium-ion battery (the temperature at which the self-heating temperature rise is greater than 1° C. / min) is greater than or equal to 253.2° C.

[0052] Compared with the prior art, the present invention has the following technical advantages:

[0053] The lithium nickelate positive electrode material of the present invention has a thermodynamically stable α-NaFeO2 hexagonal layered structure, the space group of its crystal structure is R-3m, and it does not contain Li2NiO3 units with a space group of c / 2m. It overcomes the defect that traditional positive electrode materials cannot simultaneously meet excellent cycle stability and high rate performance. The lithium nickelate positive electrode material of the present invention has high cycle stability, high rate performance and high thermal stability.

[0054] The present invention introduces a slightly excess of lithium ions in the stoichiometric ratio into the nickel layer in the layered structure of lithium nickelate by a molten salt chemistry method, and obtains a slightly lithium-rich lithium nickelate positive electrode material without changing the layered crystal structure. When the positive electrode of the lithium nickelate is used in a lithium ion battery, the lithium ion battery is charged to 4.3V (vs Li + / Li) can achieve an energy density of >900Wh / kg, and both cycle stability and rate performance are excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1, neutron diffraction test results of positive electrode material 1 in Example 1;

[0056] FIG2 is a scanning transmission electron microscope photograph of the positive electrode material 1 in Example 1;

[0057] FIG3 , electrochemical charge-discharge test results of positive electrode material 1 in Example 1 and positive electrode material 1 in Comparative Example 1;

[0058] FIG4 is a diagram showing rate test results of positive electrode material 1 in Example 1 and positive electrode material 1 in Comparative Example 1;

[0059] Figure 5 is the first charge-discharge curve of the positive electrode material 1 in Example 1;

[0060] FIG6 shows thermal safety test results of positive electrode material 1 in Example 1 and positive electrode material 1 in Comparative Example 1 in a charged state;

[0061] FIG7 shows oxygen release test results of cathode material 1 in Example 1 and conventional lithium-deficient lithium nickelate in the prior art;

[0062] FIG8 is a scanning transmission electron microscopy image of the positive electrode material 1 in Example 1;

[0063] Figure 9: Neutron diffraction pattern of the positive electrode material in Comparative Example 6. DETAILED DESCRIPTION

[0064] Lithium nickel oxide (LiNiO2) has a high energy density (>900Wh / kg). However, it is difficult to obtain a phase that conforms to the theoretical stoichiometric ratio during synthesis of this material, and it is usually lithium-deficient (the ratio of the amount of Li and Ni is less than 1). During electrochemical cycling, this material is prone to structural transformation from a layered phase to a rock salt phase and is also prone to loss of lattice oxygen, resulting in poor cycling stability. This structural transformation also leads to poor rate performance.

[0065] Traditional lithium nickelate is usually prepared by solid-state reaction, and the obtained lithium-deficient lithium nickelate has the chemical formula Li 1-y Ni 1+y O2, in order to improve the performance of lithium nickelate, the structure is usually modified by lattice doping or surface coating.

[0066] The chemical formula is Li 1+x Ni 1-x O2-rich lithium nickel oxide positive electrode materials cannot be prepared by traditional solid-state reaction preparation methods. Although the phase of this material is predicted to be a possible phase based on the Li-Ni-O phase diagram, it cannot be actually prepared through experiments.

[0067] Although there are other types of lithium-rich positive electrode materials in the prior art, the ratio of the amount of Li and transition metal in such materials is usually greater than 1.1:0.9. However, in the crystal structure of such materials, in addition to the layered R-3m structural unit, there is also a c / 2m (monoclinic structure Li2NiO3) structural unit. As a result, although such materials can achieve high energy density under high pressure, their cycle stability is poor.

[0068] The present invention creatively uses a molten salt chemical method to add a molten salt additive when synthesizing lithium nickelate, and can prepare a layered structured slightly lithium-rich lithium nickelate positive electrode material containing only R-3m structural units, whose chemical formula is Li 1+x Ni 1-x When the positive electrode material is used in lithium-ion batteries, the lithium-ion batteries have high energy density, excellent cycle stability and thermal stability.

[0069] Example 1

[0070] Mix Ni(OH)2 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.3:0.27), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.2 liters / minute, increase the temperature to 600 degrees at a rate of 5 degrees / minute, keep it at 600 degrees for 15 hours, and then cool it to room temperature at a rate of 5 degrees / minute.

[0071] The cooled powder was removed, mechanically crushed, and deionized water was added to dissolve excess LiOH and Li2SO4. The solid portion was filtered and dried at 60°C with air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.2 L / min. The temperature was raised to 500°C at a rate of 5°C / min. After maintaining the temperature at 500°C for 5 hours, the temperature was then lowered to room temperature at a rate of 5°C / min to obtain positive electrode material 1.

[0072] The crystal structure of the positive electrode material 1 was characterized by neutron diffraction (Figure 1), confirming that it is a layered structure with a space group of R-3m and does not contain c / 2m Li2NiO3 units because no superstructure peak was observed, where the superstructure refers to the in-plane superstructure caused by the orderly arrangement of Li and Ni to form Li@Ni6 in the Ni layer. The superstructure corresponds to the Li2NiO3 unit with c / 2m symmetry. Scanning transmission electron microscopy was further used to confirm that the excess Li ions were randomly distributed in the Ni layer. The results of scanning transmission electron microscopy are shown in Figure 8. Since Li is lighter than Ni, the contrast is darker. It can be seen from Figure 8 that the darker points correspond to the presence of Li atoms that replace Ni in the Ni layer, and they are randomly distributed (as indicated by the arrows in Figure 8). Scanning transmission electron microscopy imaging also confirmed that the material has a layered structure (Figure 2). The elemental composition of the material was analyzed using ICP, confirming that the amount of matter ratio of Li and Ni is 1.04:0.96 (i.e., the chemical formula Li 1+x Ni 1-x O2, x = 0.04), the results are shown in Table 1.

[0073] Example 2

[0074] Mix Ni(OH)2 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.1:0.27), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.5 liters / minute, and heat it to 650 degrees at a rate of 2 degrees / minute. After keeping it at 650 degrees for 15 hours, cool it to room temperature at a rate of 2 degrees / minute.

[0075] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve excess LiOH and Li2SO4. The solid fraction was filtered and dried at 60°C with forced air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.5 liters / minute. The temperature was raised to 450°C at a rate of 2°C / minute. After maintaining the temperature at 450°C for 2 hours, the temperature was then lowered to room temperature at a rate of 2°C / minute to obtain cathode material 2. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0076] Example 3

[0077] Mix Ni(OH)2 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.7:0.27), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.1 liters / minute, increase the temperature to 550 degrees at a rate of 10 degrees / minute, keep it at 550 degrees for 15 hours, and then cool it to room temperature at a rate of 10 degrees / minute.

[0078] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve excess LiOH and Li2SO4. The solid fraction was filtered and dried at 60°C with forced air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.1 L / min, and the temperature was raised to 550°C at a rate of 10°C / min. After maintaining the temperature at 550°C for 4 hours, the temperature was then lowered to room temperature at a rate of 10°C / min to obtain cathode material 3. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0079] Example 4

[0080] Mix Ni(OH)2 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.5:0.1), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.2 liters / minute, increase the temperature to 600 degrees at a rate of 5 degrees / minute, keep it at 600 degrees for 15 hours, and then cool it to room temperature at a rate of 5 degrees / minute.

[0081] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve excess LiOH and LiSO. The solid fraction was filtered and dried at 60°C with forced air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.2 L / min, and the temperature was raised to 500°C at a rate of 5°C / min. After maintaining the temperature at 500°C for 5 hours, the temperature was then lowered to room temperature at a rate of 5°C / min to obtain cathode material 4. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0082] Example 5

[0083] Mix Ni(OH)2 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.5:0.5), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.2 liters / minute, increase the temperature to 600 degrees at a rate of 5 degrees / minute, keep it at 600 degrees for 15 hours, and then cool it to room temperature at a rate of 5 degrees / minute.

[0084] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve excess LiOH and LiSO. The solid fraction was filtered and dried at 60°C with forced air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.2 L / min, and the temperature was raised to 500°C at a rate of 5°C / min. After maintaining the temperature at 500°C for 5 hours, the temperature was then lowered to room temperature at a rate of 5°C / min to obtain cathode material 5. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0085] Example 6

[0086] NiO was mixed evenly with LiOH·H2O and Li2SO4 (the molar ratio of the three was 1:1.3:0.27), and then the mixed powder was added to a corundum porcelain boat, placed in a tube furnace, and pure oxygen was introduced at a flow rate of 0.2 liters / minute. The temperature was raised to 600 degrees at a rate of 5 degrees / minute. After keeping at 600 degrees for 15 hours, the temperature was lowered to room temperature at a rate of 5 degrees / minute.

[0087] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve the excess LiOH·H₂O and Li₂SO₄. The solid fraction was filtered and air-dried at 60°C. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.2 L / min, and the temperature was raised to 500°C at a rate of 5°C / min. After maintaining the temperature at 500°C for 5 hours, the temperature was then lowered to room temperature at a rate of 5°C / min to obtain cathode material 6. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0088] Example 7

[0089] Mix NiCO3 with LiOH and Li2SO4 evenly (the ratio of the amount of substances among the three is 1:1.3:0.27), then add the mixed powder into a corundum porcelain boat, put it into a tube furnace, introduce pure oxygen at a flow rate of 0.2 liters / minute, increase the temperature to 600 degrees at a rate of 5 degrees / minute, keep it at 600 degrees for 15 hours, and then cool it to room temperature at a rate of 5 degrees / minute.

[0090] The cooled powder was then removed and mechanically crushed, followed by addition of deionized water to dissolve excess LiOH and LiSO. The solid fraction was filtered and dried at 60°C with forced air. The dried powder was again added to a corundum boat and placed in a tube furnace. Pure oxygen was introduced at a rate of 0.2 L / min, and the temperature was raised to 500°C at a rate of 5°C / min. After maintaining the temperature at 500°C for 5 hours, the temperature was then lowered to room temperature at a rate of 5°C / min to obtain cathode material 7. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0091] Comparative Example 1

[0092] Ni(OH)2 and LiOH were mixed evenly (the molar ratio between the two was 1:1.02), and then the mixed powder was added to a corundum porcelain boat. The mixture was placed in a tube furnace, and pure oxygen was introduced at a flow rate of 0.2 liters / minute. The temperature was raised to 485 degrees at a rate of 5 degrees / minute, and the temperature was kept at this temperature for 3 hours. The temperature was then further raised to 700 degrees, kept at this temperature for 20 hours, and then cooled to room temperature at a rate of 5 degrees / minute. Comparative positive electrode material 1 was obtained. The elemental composition of the material was analyzed by ICP, and the results are shown in Table 1.

[0093] Performance testing:

[0094] Electrochemical Cycling Stability: A button cell was assembled in an argon-protected glove box with the cathode material 1 from Example 1, a lithium sheet, a separator, and an electrolyte (lithium hexafluorophosphate dissolved in dimethyl carbonate and fluoroethylene carbonate in a 1:1 volume ratio, with a lithium hexafluorophosphate concentration of 1 mol / L). The cells were charged and discharged at a 1C rate over a voltage range of 4.3-2.8 V. The cathode material 1 from Comparative Example 1 was subjected to the same procedure. The electrochemical cycling stability results are shown in Figure 3.

[0095] Rate Performance: The rate performance of the two materials was evaluated using the same button-type cells described above. After charging to 4.3V at a 0.2C rate, the cells were discharged at rates ranging from 0.5C to 10C. The test results are shown in Figure 4. The first discharge energy density of the cell corresponding to positive electrode material 1 of Example 1, as obtained by integrating the charge-discharge curves, was 904Wh / kg (Figure 5).

[0096] Example 8 (Thermal safety test)

[0097] The positive electrode material 1 of Example 1 was used to assemble a soft-pack battery for thermal safety evaluation. The assembly method is as follows: (1) Preparation of positive electrode sheet: The active material (positive electrode material 1 of Example 1), the conductive agent (carbon black) and the binder (5wt% polyvinylidene fluoride / N-methylpyrrolidone solution) are mixed in a mass ratio of 94:3:3, N-methylpyrrolidone (NMP) is added to adjust the solid content to 65%, and the mixture is coated on a 13μm aluminum foil. After drying, the mixture is punched into 55mm*35mm (H*W) electrode sheets using a punching machine, and the mixture is rolled and vacuum-dried at 120℃ for 12 hours; (2) Preparation of negative electrode sheet: The active material (graphite), the conductive agent (carbon black) and the binder (5wt% polyvinylidene fluoride / N-methylpyrrolidone solution) are mixed in a mass ratio of 94:3:3, NMP is added to adjust the solid content to 45%, and the mixture is coated on a 10μm copper foil. After drying, the mixture is punched into 57mm*37mm (H*W) electrode sheets using a punching machine, and the mixture is rolled and vacuum-dried at 80℃ for 12 hours. (3) Production of soft-pack cells: 16μm PE diaphragm and positive and negative electrodes are stacked to form a cell, ensuring that each positive electrode has a corresponding negative electrode. The outermost layer is wrapped with a diaphragm and then glued with polyimide tape. Use an ultrasonic welding machine to weld the aluminum and nickel tabs to the exposed tabs of the positive and negative electrodes respectively. Use polyimide tape to stick the welds. Wrap the outer layer of the cell with aluminum plastic film and leave an opening for injecting electrolyte. The prepared cell is vacuum-dried at 60℃ for 6 hours. The cell capacity is set to 30mAh. (4) Battery production: Use a pipette to inject 0.5g of electrolyte (the electrolyte composition is 1.2M lithium hexafluorophosphate solution, the solvent is a mixed solvent of ethylene carbonate EC and ethyl methyl carbonate EMC with a weight ratio of 3:7, and the solvent contains 2% by mass of vinylene carbonate VC) into the cell, and seal the injection port with a sealing machine. Lay it flat and let it stand for 10 hours before testing. (5) Battery formation and testing: After clamping the battery with a fixture, test it on a charge and discharge tester. Use a constant current of 0.1C (22mA / g, based on the mass of the positive electrode active material, the same below) to charge to 4.25V and a constant voltage of 0.05C. Use a 0.1C discharge to 2.75V. Repeat the above steps three times to complete the battery formation.

[0098] The thermal safety evaluation method involves charging two prefabricated soft-pack batteries at a constant current of 0.1C to 4.25V, then charging them at a constant voltage of 0.05C before use. The accelerometer chamber is opened, and the tip of a thermocouple is attached to the center of one battery using aluminum tape. The other battery is then placed on top of the other battery, and the two batteries are taped together using aluminum tape before being secured to a dedicated test stand within the chamber. The accelerometer cover is closed, and the accelerometer program is activated for testing. The specific test procedure is as follows: Starting at 25°C, the chamber is heated in heating mode, heating the chamber in 10-minute increments of 5°C. The temperature is then monitored for 30 minutes, followed by a search mode. During this period, if the temperature rise rate is less than 0.02°C / min, heating is resumed after the rest period. If the temperature rise rate is greater than 0.02°C / min, the chamber enters the exothermic mode, discontinuing heating and recording the temperature change. Once the temperature exceeds 300°C, the chamber enters the cooling mode, completing the test. The test results are shown in Figure 6. The battery equipped with the positive electrode material 1 of Example 1 has a relatively high T2 temperature (thermal runaway temperature, the temperature at which the self-heating temperature rise is greater than 1 degree / min), which is 253.2 degrees.

[0099] Comparative Example 2 (Thermal Safety Test)

[0100] The assembly method and thermal safety evaluation method for the soft-pack battery were the same as those for Example 8, except that the positive electrode material 1 of Example 1 was replaced with the comparative positive electrode material 1 of Comparative Example 1. The test results are shown in Figure 6 , showing a T2 temperature (thermal runaway temperature, the temperature at which the self-heating temperature rise exceeds 1°C / min) of 179.0°C. Therefore, Comparative Example 2 is more susceptible to thermal runaway than Example 8.

[0101] In situ differential electrochemical mass spectrometry DEMS was used to test the oxygen and carbon dioxide release of the lithium nickelate positive electrode material of Example 1 and the conventional lithium-deficient lithium nickelate positive electrode material in the prior art. The test conditions were the first charge and the charge rate was 0.1C. The results are shown in Figure 7, where A is conventional lithium nickelate (LNO) and B is the lithium nickelate of Example 1 (slightly lithium-rich LR-LNO). It can be seen that in conventional lithium nickelate, 4.2 μmol / g of O2 and 86.5 μmol / g of CO2 are generated during delithiation, while the lithium nickelate of Example 1 basically does not release oxygen.

[0102] Example 9

[0103] The process is basically the same as Example 1, except that Li2SO4 is replaced by Na2SO4.

[0104] Example 10

[0105] The process is basically the same as Example 1, except that Li2SO4 is replaced by K2SO4.

[0106] Comparative Example 3

[0107] Basically the same as Example 1, the only difference is that Li2SO4 is not added.

[0108] Comparative Example 4

[0109] The process is basically the same as Example 1, except that the ratio of the amounts of Ni(OH)2, LiOH and Li2SO4 is 1:1.05:0.27.

[0110] Comparative Example 5

[0111] The process is basically the same as Example 1, except that the ratio of the amounts of Ni(OH)2, LiOH and Li2SO4 is 1:2:0.27.

[0112] Comparative Example 6

[0113] The solution of the embodiment in JP2015082345A is as follows:

[0114] Lithium peroxide (Li2O2) and nano-sized nickel oxide were used as starting materials. These materials were crushed and mixed to a molar ratio of Li / Ni=1.9. The mixture was filled into a platinum tank and sintered at 700°C for 1 hour under a pressure of 4GPa using a cubic anvil high-pressure device to obtain lithium-rich lithium nickelate. The average particle size was about 50 to 100nm. The element content was analyzed by ICP emission spectroscopy, confirming that its composition was Li 1.30 Ni 0.70 Figure 2 (neutron diffraction pattern) of the patent is shown in Figure 9, which shows that the cathode material has a layered structure. In addition to the R-3m space group, it also contains c / 2m Li2NiO3 units. Because there is a very obvious superstructure peak in Figure 9 (2θ is located in the range of 20-25 degrees, corresponding to the dotted box), it corresponds to the c / 2m Li2NiO3 (here M = Ni) unit, that is, the orderly arrangement of Li@Ni6 in the Ni layer.

[0115] The elemental compositions of the materials of Examples 9-10 and Comparative Examples 3-5 were analyzed using ICP. The results are shown in Table 1.

[0116] Table 1. Elemental analysis results of Examples and Comparative Examples

Claims

1. A lithium nickelate positive electrode material, characterized in that The chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-x O2, wherein 0.02≤x≤0.08; the crystal structure of the lithium nickelate positive electrode material is an α-NaFeO2 type hexagonal layered structure, and the space group of the crystal structure of the lithium nickelate positive electrode material is R-3m type; in the crystal structure of the lithium nickelate positive electrode material, Li that is in excess relative to the stoichiometric ratio of Ni occupies the octahedral voids in the Ni layer in the layered structure and is randomly distributed in the octahedral voids.

2. The lithium nickelate positive electrode material according to claim 1, characterized in that 0.03≤x≤0.06。 3. The lithium nickelate positive electrode material according to claim 1, characterized in that 0.04≤x≤0.05。 4. A lithium nickelate positive electrode material, characterized in that The chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-x O2, wherein 0.02≤x≤0.08; the crystal structure of the lithium nickelate positive electrode material is an α-NaFeO2 type hexagonal layered structure, and the space group of the crystal structure is R-3m type.

5. The lithium nickelate positive electrode material according to claim 4, characterized in that In the crystal structure of the lithium nickelate positive electrode material, Li, which is in excess relative to Ni in a stoichiometric ratio, occupies the octahedral voids in the Ni layer in the layered structure and is randomly distributed in the octahedral voids.

6. The lithium nickelate positive electrode material according to claim 1 or 4, characterized in that Neutron diffraction analysis revealed that no Li2NiO3 unit with space group c / 2m was detected in the crystal structure.

7. A lithium nickelate positive electrode material, characterized in that The chemical formula of the lithium nickelate positive electrode material is Li 1+x Ni 1-x O2, wherein 0.02≤x≤0.08, the lithium nickelate positive electrode material is prepared by a preparation method comprising the following steps: (1) reacting a nickel source and a lithium source with oxygen in the presence of a molten salt additive to obtain a product containing lithium nickelate; (2) purifying the product containing lithium nickelate to obtain a powder containing lithium nickelate, and placing the powder in an oxygen environment to obtain the lithium nickelate positive electrode material.

8. A method for preparing the lithium nickelate positive electrode material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) reacting a nickel source and a lithium source with oxygen in the presence of a molten salt additive to obtain a product containing lithium nickelate; (2) Purifying the product containing lithium nickelate to obtain a powder containing lithium nickelate, and placing the powder in an oxygen environment to obtain the lithium nickelate positive electrode material.

9. The method according to claim 8, characterized in that The nickel source is selected from one or more of NiO, Ni(OH)2 or NiCO3.

10. The method according to claim 8, characterized in that The lithium source is selected from LiOH or LiOH·H2O.

11. The method according to claim 8, characterized in that The molten salt additive is selected from one or more of Li2SO4, Na2SO4 and K2SO4.

12. The method according to claim 8, characterized in that The molten salt additive is Li2SO4.

13. The method according to claim 8, characterized in that The molar ratio of the lithium source to the nickel source is 1.1-1.7:1; and / or the molar ratio of the molten salt additive to the nickel source is 0.1-0.5:

1.

14. The method according to claim 8, characterized in that The molar ratio of the lithium source to the nickel source is 1.3-1.5:1; and / or the molar ratio of the molten salt additive to the nickel source is 0.27-0.5:

1.

15. The method according to claim 8, characterized in that In step (1), the reaction temperature is 550-650°C; and / or, in step (1), the reaction time is 10-20 hours; and / or, in step (2), the temperature of the oxygen environment is 450-550°C; and / or, in step (2), the time of being placed in the oxygen environment is 2-5 hours.

16. The method according to claim 8, characterized in that In step (2), the purification includes washing with water and filtering; and / or the method further includes a step of crushing the product containing lithium nickelate before the purification.

17. The method according to claim 8, characterized in that The method comprises the following steps: (1) uniformly mixing a nickel source, a lithium source, and a molten salt additive to obtain a mixture, placing the mixture in a reactor, introducing oxygen into the reactor, and heating the reactor to react to obtain a product containing lithium nickelate; (2) The product containing lithium nickelate is crushed, washed with water, and filtered to obtain a powder containing lithium nickelate, the powder is placed in a reactor, oxygen is introduced into the reactor, and the temperature is increased to obtain the lithium nickelate positive electrode material.

18. The method according to claim 17, characterized in that In step (1), the flow rate of the oxygen is 0.1-0.5 L / min; and / or, in step (1), the heating rate is 2-10° C. / min.

19. The method according to claim 17, wherein In step (2), the flow rate of the oxygen is 0.1-0.5 L / min; and / or, in step (2), the heating rate is 2-10° C. / min.

20. Use of the lithium nickelate positive electrode material according to any one of claims 1 to 7 in a lithium ion battery.

21. A lithium ion battery comprising a positive electrode, characterized in that: The positive electrode comprises the lithium nickelate positive electrode material according to any one of claims 1 to 7.

22. The lithium-ion battery according to claim 21, wherein The lithium-ion battery has an initial discharge energy density greater than or equal to 904Wh / kg at a rate of 0.1C; and / or, after 100 charge and discharge cycles within a voltage range of 4.3-2.8V at a rate of 1C, the lithium-ion battery has a discharge specific capacity retention rate greater than or equal to 92.3%.